Tissue Adaptations of Memory and Tissue-Resident Gamma Delta T Cells - Khairallah, Camille; Chu, Timothy H.; Sheridan, Brian S. (Frontiers in Immunology, 2018)
Epithelial and mucosal barriers are critical interfaces physically separating the body from the outside environment and are the tissues most exposed to microorganisms and potential inflammatory agents. The integrity of these tissues requires fine tuning of the local immune system to enable the efficient elimination of invasive pathogens while simultaneously preserving a beneficial relationship with commensal organisms and preventing autoimmunity. Although they only represent a small fraction of circulating and lymphoid T cells,  T cells form a substantial population at barrier sites and even outnumber conventional  T cells in some tissues. After their egress from the thymus, several  T cell subsets naturally establish residency in predetermined mucosal and epithelial locations, as exemplified by the restricted location of murine V5+ and V3V1+ T cell subsets to the intestinal epithelium and epidermis, respectively. More recently, a growing body of studies have shown that  T cells form long-lived memory populations upon local inflammation or bacterial infection, some of which permanently populate the affected tissues after pathogen clearance or resolution of inflammation. Natural and induced resident  T cells have been implicated in many beneficial processes such as tissue homeostasis and pathogen control, but their presence may also exacerbate local inflammation under certain circumstances. Further understanding of the biology and role of these unconventional resident T cells in homeostasis and disease may shed light on potentially novel vaccines and therapies.